Agroforestry in the European common agricultural policy - Mosquera-Losada, María Rosa; Santiago-Freijanes, Jose Javier; Pisanelli, Andrea; Rois-Díaz, Mercedes; Smith, J.; den Herder, Michael; Moreno, Gerardo; Ferreiro-Domínguez, N.; Malignier, Nina; Lamersdorf, Norbert; Balaguer, Fabien; Pantera, Anastasia; et al. (Springer, 2018)
Agroforestry is a sustainable land management system that should be more strongly promoted in Europe to ensure adequate ecosystem service provision in the old continent (Decision 529/2013) through the common agricultural policy (CAP). The promotion of the woody component in Europe can be appreciated in different sections of the CAP linked to Pillar I (direct payments and Greening) and Pillar II (rural development programs). However, agroforestry is not recognised as such in the CAP, with the exception of the Measure 8.2 of Pillar II. The lack of recognition of agroforestry practices within the different sections of the CAP reduces the impact of CAP activities by overlooking the optimum combinations that would maximise the productivity of land where agroforestry could be promoted, considering both the spatial and temporal scales.
Keywords: Pillar I; Pillar II; Greening; Rural development programs; Cross-compliance